Genetic rearrangement during site specific integration event facilitates cell line development of a bispecific molecule. (12th May 2021) - Tevelev, Barbara; Patel, Himakshi; Shields, Kathleen; Wei, Wei; Cooley, Cecilia; Zhang, Sam; Bitzas, Gabrielle; Duan, Weili; Khetemenee, Lam; Jackobek, Ryan; D'Antona, Aaron; Sievers, Annette; et al.
Abstract: Site specific integration (SSI) expression systems offer robust means of generating highly productive and stable cell lines for traditional monoclonal antibodies. As complex modalities such as antibody‐like molecules comprised of greater than two peptides become more prevalent, greater emphasis needs to be placed on the ability to produce appreciable quantities of the correct product of interest (POI). The ability to screen several transcript stoichiometries could play a large role in ensuring high amounts of the correct POI. Here we illustrate implementation of an SSI expression system with a single site of integration for development and production of a multi‐chain, bi‐specific molecule. A SSI vector with a single copy of all of the genes of interest was initially selected for stable Chinese hamster ovary transfection. While the resulting transfection pools generated low levels of the desired heterodimer, utilizing an intensive clone screen strategy, we were able to identify clones having significantly higher levels of POI. In‐depth genotypic characterization of clones having the desirable phenotype revealed that a duplication of the light chain within the landing pad was responsible for producing the intended molecule. Retrospective transfection pool analysis using a vector configuration mimicking the transgene configuration found in the clones, as well as other vector configurations, yielded more favorable results with respect to % POI. Overall, the study demonstrated that despite the theoretical static nature of the SSI expression system, enough heterogeneity existed to yield clones having significantly different transgene phenotypes/genotypes and support production of a complex multi‐chain molecule.